Acoustic Nonlinearity Parameter B/A, Internal Pressure, and Acoustic Impedance Determined at Pressures up to 100 MPa for 1-Ethyl-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]imide - ZORĘBSKI, Edward; ZORĘBSKI, Michał; DZIDA, Marzena (Archives of Acoustics, 2016)
The nonlinearity parameter B/A, internal pressure, and acoustic impedance are calculated for a room temperature ionic liquid, i.e. for 1-ethyl-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]imide for temperatures from (288.15 to 318.15) K and pressures up to 100 MPa. The B/A calculations are made by means of a thermodynamic method. The decrease of B/A values with the increasing pressure is observed. At the same time B/A is temperature independent in the range studied. The results are compared with corresponding data for organic molecular liquids. The isotherms of internal pressure cross at pressure in the vicinity of 70 MPa, i.e. in this range the internal pressure is temperature independent.